Restructuring reforms for green growth - Cevik, Serhan (2023)
Policymakers across the world are striving to tackle the century-defining challenge of climate change without undermining potential growth. This paper examines the impact of structural reforms in the energy sector (electricity and gas) on enviromental outcomes and green growth indicators in a panel of 25 advanced economies during the period 1970-2020. We obtain striking results. First, while structural reforms so far failed in reducing greenhouse gas emissions per capita, there is some evidence for greater effectiveness in lowering emissions per unit of GDP. Second, although energy reforms are not associated with higher supply of renewable energy as a share of total energy supply, they appear to stimulate a sustained increase in environmental inventions and patents per capita over the medium term. We also find strong evidence of nonlinear effects, with market-friendly energy reforms leading to better environmental outcomes and green growth in countries with stronger environmental regulations. Looking forward, therefore, structural reforms should be designed not just for market efficiency but also for green growth.